Analisis Pengaruh biaya dan Lokasi Terhadap keputusan Mahasiswa Memilih Universitas Terbuka (Studi Pada mahasiswa UPBJJ-UT Pontianak) - Fahri Ansyah; Edward Zubir (STIE 'INDONESIA' Pontianak, 2015)
The title of this research is the analysis of the effect of the cost and the location on the students’ decision to study in Open University (The study conducted on student-UT UPBJJ Pontianak). The background of this research is the declining level of participation of UPBJJ-UT Pontianak students, hence the researchers tried to find whether the cost and location variables affect the level of student participation. Based on this research background, the research problems of this study is to what extent the costs and location influence the student's decision to study at UT in Pontianak UPBJJ either partially or simultaneously. The benefits expected from the findings of this study is to provide information to the unit of work, authors and academics management in decision-making to enhance the student participation as well as a reference for other researchers who also studying the other variables that affect the number of students participation in UPBJJ UT Pontianak. The research method in this study using a survey method in which the population of this study were all students of UPBJJ-UT Pontianak, the sample size of this study were 150 respondents from all existing populations. The results of this study showed that costs affect the student's decision in choosing a lecture at UT UPBJJ Pontianak significantly and for the location variables the influence is not significant, while in simultaneously both variables influence the student's decision significantly.